Quantification of sphingosine-1-phosphate (S1P) in patientswith periodontitis stage II grade B = Cuantificación de esfingosina 1 fosfato en pacientescon periodontitis estadío II grado B - García-Parra, María I.; Jiménez Coello, Matilde; Carrillo Ávila, Bertha A.; Sauri Esquivel, Eduardo A.; Martínez Aguilar, Víctor Manuel (2022)
The aim of this study was the quantification of Sphingosine-1-phosphate (S1P) in periodontal pockets of patients with periodontitis. This is an observational, descriptive, case-control study. Thirty subjects were selected: 15 controls and 15 cases. A periodontal study was conducted following the parameters of AAP 2017 for the diagnosis of periodontal diseases. A sample of saliva and gingival crevicular fluid was obtained from each subject and then analyzed with the Human S1P Elisa kit (MyBioSource #MBS2516132) accordingly to the manufacturer's instructions, in order to verify the presence of S1P and quantify it's concentration when founded. Results showed a significant difference (p=0.05) between cases and controls. In the case of saliva samples, the concentration of S1P was higher than the ones found in the control group (72.94 ng/mL and 45.12 ng/mL). For GCF, a higher amount of S1P was found in patients with POD (20.09 ng/mL and 15.20 ng/mL). This work raises a possible route of bone metabolism, inflammatory process, and identification of periodontitis through oral quantification of S1P, however, future studies are needed.
El propósito de este estudio fue la cuantificación de Esfingosina-1-Fosfato (S1P) en las bolsas periodontales de pacientes con periodontitis. Estudio observacional, descriptivo de casos y controles. 30 sujetos fueron seleccionados de los cuales 15 controles y 15 casos. Se realizó un estudio periodontal completo siguiendo los parámetros establecidos por la AAP en 2017 para el diagnóstico de las enfermedades periodontales. Se tomaron muestras de saliva y de líquido crevicular gingival de cada sujeto estudiado y se analizaron con el ELISA kit humano para S1P (MyBiosource #MBS2516132) y de acuerdo con las instrucciones del fabricante, se realizó para cuantificar la presencia d S1P en las muestras estudiadas. Los resultados mostraron diferencia significativa (p=0.05) entre casos y controles. En el caso de las muestras de saliva, la concentración de S1P en controles fue mayor (72.94 ng/mL y 45.12 ng/mL). Para Líquido crevicular gingival, se encontró mayor cantidad de S1P en los pacientes con periodontitis (20.09 ng/mL y 15.20 ng/mL). Este estudio plantea una posible ruta de metabolismo óseo, proceso inflamatorio e identificación de la Periodontitis a través de la cuantificación oral de S1P, sin embargo se necesitan estudios futuros.
En revista Odóvtos, vol. 24, no.1 (enero-abril 2022)
Descripción basada en el contenido visto el 15 de noviembre, 2024
También disponible en formato HTML y EPUB